Optimization Models for the Control of Saltwater Intrusion - Robert Willis (Institute for Research and Community Services (LPPM) ITB, 2013)
A general optimal control model was developed for the control of saltwater intrusion in coastal aquifer systems. The underlying sharp-interface and density-dependent hydraulic and water quality response equations are presented. Different solution algorithms are described for the control problem, including the imbedding method, Box's algorithms, and the linked simulation-optimization methodology (LSO). Several field applications are presented. The optimization approach, despite requiring significant computation resources, is superior to conventional simulation methods. Optimization produces not only locally optimal planning, design, and operational policies, but also tradeoffs associated with environmental and hydraulic objectives.